Cobalt (II), Nickel (II) and Copper (II) Complexes of 1, 5-Benzodiazepines: Synthesis, Spectral and Magnetochemical Studies - Prabhakar, B.K.; Kuldarni, V.H. (Asian Journal of Chemistry, 2010)
Complexes of benzodiazepines of the 1 : 2 stoichiometry of the type ML2Cl2 [where M ═ Co(II), Ni(II) or Cu(II) and L ═ 7-substituted-2, 4-dimethyl-6,7-benz-1,5-diazepines (I-IV)] have been synthesised and characterised by molar conductance, magnetic moments, infrared, electro nic and X-ray studies. The infrared spectral data support the involvement of both nitrogen atoms in the complex formation. All the observations favour tetrahedral configuration for cobalt(II), nickel(II) and square planar configuration for copper(II).